Numerical Evaluation of Multi-layered Solid-PCM Thermocline-like Tanks as Thermal Energy Storage Systems for CSP Applications. (May 2015) - Galione, P.; Pérez-Segarra, C.; Rodríguez, I.; Torras, S.; Rigola, J.
Abstract: The two-tank system is the technology used for thermal energy storage (TES) in current concentrating solar power (CSP) plants. Thermocline storage concept has been considered for more than a decade as a possible solution to reduce the high cost of the storage system in these plants. In previous works, multi-layered solid-PCM (MLSPCM) thermocline-like storage tank configurations has been introduced and studied, giving promising results for their use as thermal energy storage systems for CSP. In this work, further analysis is performed in the use of this new concept of TES, by considering variable inlet conditions, and simulating the tank shell and the foundation. The numerical simulations are based on a modular object-oriented methodology. Energetic and exergetic results are presented and compared against a reference 2-tank case and against different thermocline configurations with either solid or phase change filler materials. Again, promising results are obtained for the tested MLSPCM concept.